2017
DOI: 10.1177/1933719116657190
|View full text |Cite
|
Sign up to set email alerts
|

Panel of Autoimmune Markers for Noninvasive Diagnosis of Minimal-Mild Endometriosis: A Multicenter Study

Abstract: Endometriosis, characterized by the presence of endometrial-like tissue at extrauterine sites, is a common, chronic, estrogen-dependent, inflammatory condition associated with pelvic pain, subfertility, dysmenorrhea, and dyspareunia, affecting about 10% of reproductive-age women in any population. The diagnosis of endometriosis is usually delayed on an average by 8 to 11 years leading to significant consequences in terms of disease progression. The current study was aimed to validate enzyme-linked immunosorben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 40 publications
2
28
0
1
Order By: Relevance
“…TMODs are also able to influence positively dendritic arbor, indeed overexpression of both TMOD1 and TMOD2 increased dendritic complexity and the branching [ 16 ]. Recently, TMODs are emerging as new protagonists in several diseases pathogenesis; TMOD2 has altered expression in fetal Down syndrome [ 17 ], mesial temporal lobe epilepsy [ 18 ], post-stroke [ 19 ] and post-methamphetamine exposure [ 20 ], while TMOD3 has been reported as a novel biomarker with high sensitivity and diagnostic accuracy in endometriosis [ 21 ]. Initial studies reported TMODs role in cancer; Kureha and colleagues [ 22 ] demonstrated that TMOD1 expression was directly regulated by NF-κB and its overexpression was associated with enhanced breast tumor growth in a mouse xenograft model.…”
Section: Introductionmentioning
confidence: 99%
“…TMODs are also able to influence positively dendritic arbor, indeed overexpression of both TMOD1 and TMOD2 increased dendritic complexity and the branching [ 16 ]. Recently, TMODs are emerging as new protagonists in several diseases pathogenesis; TMOD2 has altered expression in fetal Down syndrome [ 17 ], mesial temporal lobe epilepsy [ 18 ], post-stroke [ 19 ] and post-methamphetamine exposure [ 20 ], while TMOD3 has been reported as a novel biomarker with high sensitivity and diagnostic accuracy in endometriosis [ 21 ]. Initial studies reported TMODs role in cancer; Kureha and colleagues [ 22 ] demonstrated that TMOD1 expression was directly regulated by NF-κB and its overexpression was associated with enhanced breast tumor growth in a mouse xenograft model.…”
Section: Introductionmentioning
confidence: 99%
“…However, none of the AAb biomarkers tested were effective [86]. A recent study reported better sensitivity of 6 new biomarkers [87]. With detection of AAbs to steroid producing cells and thyroglobulin in cases with concomitant adrenal or thyroid disease in PCOS, it is now considered an autoimmune disease.…”
Section: Female Autoimmune Infertilitymentioning
confidence: 99%
“…Stomatin-like protein 2 [84,87] Tropomodulin 3 (TMOD3) fact that these were NAbs. These were also validated to induce aPOI in a mouse model.…”
Section: Hspa5 (Hsp70)mentioning
confidence: 99%
“…It is also possible that some of these developmental defects may originate from earlier defects in asymmetric division during oocyte maturation, discussed above. Nevertheless, growing evidence from exploratory expression/biomarker studies demonstrates likely Tmod3 involvement in other specialized cellular phenomena (Lopez-Ubeda et al 2015;Lu et al 2017;Paez et al 2016;Qiu et al 2010) and pathologies (Gajbhiye et al 2017;Gajbhiye et al 2012;Paez et al 2016), providing evidence of Tmod3's broad and relatively unexplored roles.…”
Section: Tmod3 Regulation Of F-actin In Embryonic Developmentmentioning
confidence: 99%